Diversity and primary productivity of hill beech forests from Doftana Valley (Romanian Subcarpathians) - Mihaela Paucã-Comãnescu; Marilena Onete; Vasile Sanda; Ioana Vicol; Ioana Onuț; Daniela Mogâldea; Sorin Ștefãnuț Ștefãnuț (Annals of Forest Research, 2009)
The hill beech forests cover most of the woody area in the Doftana Valley. The present study refers, for the first time, to two beech forests typical to this belt, which belong to the phytocoenological associations Epipactieto-Fagetum (Resmeriţă, 1972), in the Lunca Mare area, and Hieracio rotundati-Fagetum (Vida 1983, Täuber 1987) in the Sotrile area, from floristic, structural, biomass and necromass accumulation point of view, within the framework of the vertical structure of biocoenosis. The limestone substratum, occasionally with small outcrops in the first beech forest, differs chiefly through the pH levels (6.34-5.67) from the siliceous substratum (pH 5.11-4.36) in the second beech forest. The layer of trees is dominated by Fagus sylvatica in both forests; this species is associated with Cerasus avium (4.5%), Acer pseudoplatanus (2%) and Sorbus torminalis (2%) in the first beech forest, and is monodominant in the second. Although the forest underwent selective cuts, more intense in the Lunca Mare area, the aboveground ligneous biomass reaches nowadays 222 t/ha in the Lunca Mare area compared to only 163 t/ha in the Sotrile area; the average height is 28.8ą2.49 m and 23.7ą1.12 m, respectively, and the diameter is 33.30ą7.9 cm and 31.60ą6.28 cm, respectively. The species of macrofungi, not very numerous during the study because of scarce precipitations (6 and 7 species, respectively), are predominant on the rhytidoma trees in the beech forest rooted on the limestone ground; in the Sotrile beech forest they are joined by mycorrhizal and parasite species. The layer of shrub is underdeveloped. The herbaceous layer is discontinuous, and includes, along herbs, small plants and saplings belonging to the ligneous species and to liana Hedera helix. The maximal value of the aboveground biomass of the layer is 317 kg/ha DM in the Lunca Mare area and 235 kg /ha DM in the Sotrile area. Bryophyta is present in large quantities, especially in the Sotrile area, where by May it represents up to 20% of the inferior layer's biomass; on the limestone ground they do not exceed 0.5%. The most frequent are on the soil surface: Polytrichum formosum, Pogonatum nanum, Hypnum cupressiforme, Tortella tortuosa at Sotrile and, respectively Metzgeria furcata var. ulvula, Leskea nervosa , Ctenidium molluscum at Lunca Mare. In the Lunca Mare area, the most relevant herbaceous species in the structure of the biomass are Viola reichenbachiana, Festuca drymeja, Sanicula europaea and Campanula trachelium; in spring there are also Erytronium dens-canis and Lathyrus vernus. In the Sotrile area these are: Luzula luzuloides, Carex digitata, Calamagrostis arundinacea and Hieracium transsylvanicum, in both spring and autumn. Hedera helix, present especially at the surface, is the most frequent and best represented in terms of biomass in both beech forests, and in particular in the Lunca Mare site. The species characteristic to the phytocoenological association and to the alliances where these beech forests are included are representative through their biomass for the Hieracio rotundati-Fagetum association, while the orchids species characteristic to associations present on the limestone ground, although very diverse and with a great number of individuals for this taxonomic group, are not representative, neither as frequency nor as biomass or density, compared to other herbal species with a larger coenotic value, which are included in the Epipactieto-Fagetum association. The necromass accumulated in the area analyzed decays slowly, varying greatly with surface and time. It averages 4492 kg/ha in the Lunca Mare area and 4134 kg/ha in the Sotrile area. The necromass is made mostly of fallen leaves, and, at least in the Lunca Mare area, the July values are amplified by vernal herb flora.